2022
DOI: 10.3390/medicina58111662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photobiomodulation in Patients Presenting with Reticular Pseudodrusen: A Retrospective Observational Case Series Study

Abstract: Background and Objectives: The purpose of this study is to describe the effects of photobiomodulation on drusen regression with patients presenting with reticular pseudodrusen (RPD). Materials and Methods: This study is a retrospective observational case series study including patients presenting with RPD who underwent treatment by photobiomodulation. All patients underwent a complete ophthalmic examination and multimodal imaging prior to treatment, including spectral-domain optical coherence tomography (SD-OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…No progression of RPD into greater stages was observed. 18 Photobiomodulation was well tolerated, with a favorable safety and compliance profile. Compliance rates for both PBM and Sham groups were high throughout each treatment series with a higher rate noted in the PBM group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…No progression of RPD into greater stages was observed. 18 Photobiomodulation was well tolerated, with a favorable safety and compliance profile. Compliance rates for both PBM and Sham groups were high throughout each treatment series with a higher rate noted in the PBM group.…”
Section: Discussionmentioning
confidence: 97%
“…Recent ophthalmologic clinical trials, including LIGHTSITE I and II, evaluated the effect of multiwavelength PBM using the Valeda light delivery system and found improvement in clinical vision outcomes and anatomical correlates of the disease. [17][18][19] LIGHTSITE III further investigates the effects of PBM treatment in early/intermediate dry AMD.…”
mentioning
confidence: 99%
“…PBM treatment has gained interest in the field of ophthalmology due to its mechanistic actions and recent studies showing benefits in a variety of indications including age-related macular degeneration [10][11][12][13][14][15][16][17][18][19][20]. The threat of vision loss and the limited/invasive treatment strategies available in many ocular conditions, including CSCR, results in extreme stress and diminished outlook in many patients.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that PBM on reticular pseudodrusen, in five cases, showed a decreased number of stage 3 reticular pseudodrusen, which is in accordance with anatomical benefits in our study. 14 Previous reports revealed that drusen development and resolution are in a constant course of change. 3,15 Drusen resolution can leave behind GA. 3 Large dPED can also collapse and disappear without leading to additional photoreceptors and RPE disruption and loss.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that PBM on reticular pseudodrusen, in five cases, showed a decreased number of stage 3 reticular pseudodrusen, which is in accordance with anatomical benefits in our study. 14…”
Section: Discussionmentioning
confidence: 99%